Neurogenesis and pesticides: news of no new neurons - Fulvio A. Scorza; Antonio-Carlos G. de Almeida; Ana C. Fiorini; Feres Chaddad-Neto; Josef Finsterer (Arquivos de Neuro-Psiquiatria, 2024)
New hippocampal neurons are continuously generated in the adult human brain. Several studies have demonstrated that the proliferation of hippocampal cells is strongly influenced by a variety of stimuli, including pesticides exposure. These effects are particularly important because neurogenesis dysregulation could be associated with the decline of neuronal and cognitive functions and the possible development of neuropsychiatric disorders.